Customer Engagement Mediation: The Influence of Social Media Marketing, Brand Image, and Perceived Value on Purchase Decisions - Astondy Lahamazta; Nurul Qomariah; Trias Setyowati (Universitas Muhammadiyah Jember, 2026)
The housing industry has experienced rapid growth in response to the increasing demand for comfortable residential properties. This study aims to examine the effects of social media marketing, brand image, and perceived value on purchase decisions, with customer engagement serving as a mediating variable among consumers of Queen Cempaka Housing in Jember Regency. This study employed a quantitative approach using a survey method, with data collected from 95 active consumers of Queen Cempaka Housing. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to evaluate the relationships among the variables. The findings reveal that social media marketing, brand image, and perceived value significantly influence customer engagement. Furthermore, social media marketing and perceived value have direct positive effects on purchase decisions, whereas brand image does not exhibit a direct effect. However, customer engagement significantly influences purchase decisions and successfully mediates the relationships between social media marketing, brand image, perceived value, and purchase decisions. Overall, this study highlights that enhancing customer engagement through effective social media initiatives, strengthening brand image, and delivering value that aligns with consumer expectations are key factors in driving purchase decisions.